2019
DOI: 10.1248/cpb.c18-00849
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Interactions between Drugs and Aminoalkyl Methacrylate Copolymer in Solution to Enhance the Concentration of Poorly Water-Soluble Drugs

Abstract: An aminoalkyl methacrylate copolymer, Eudragit ® E (EUD-E), has gained tremendous attention as a solid dispersion carrier because it efficiently stabilizes drugs in the amorphous state. Furthermore, EUD-E remarkably enhances drug dissolution in water. This review focuses on the interaction between drugs and EUD-E in solution, which contributes to the enhancement of drug concentration. Studies examining interactions between acidic drugs and EUD-E in organic solvents have revealed that the interaction occurs pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…These are really polymeric dispersants that have been designed to enhance their dispersibility of various drugs to make them more accessible to adsorption in the body. An example is a class of methacrylate-based terpolymers mostly made up of three methacrylate monomers, butyl methacrylate, 2-dimethylaminoethyl methacrylate, and methyl methacrylate. , A methacrylate terpolymer polymer from this series was used in our study. By itself it is soluble in water or brines at pH 5–6 or less, which will make it slightly cationic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are really polymeric dispersants that have been designed to enhance their dispersibility of various drugs to make them more accessible to adsorption in the body. An example is a class of methacrylate-based terpolymers mostly made up of three methacrylate monomers, butyl methacrylate, 2-dimethylaminoethyl methacrylate, and methyl methacrylate. , A methacrylate terpolymer polymer from this series was used in our study. By itself it is soluble in water or brines at pH 5–6 or less, which will make it slightly cationic.…”
Section: Resultsmentioning
confidence: 99%
“…An example is a class of methacrylate-based terpolymers mostly made up of three methacrylate monomers, butyl methacrylate, 2-dimethylaminoethyl methacrylate, and methyl methacrylate. 40,41 A methacrylate terpolymer polymer from this series was used in our study. By itself it is soluble in water or brines at pH 5−6 or less, which will make it slightly cationic.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One example is a class of terpolymers mostly consisting of three methacrylate monomers: butyl methacrylate, 2-dimethylaminoethyl methacrylate, and methyl methacrylate (see Figure ). , The polymer by itself is soluble in water or brines at pH values of 5–6 or less. This polymer is particularly helpful at solubilization acidic drugs via ionic interactions (e.g., protonated amine moieties) and by multiple hydrophobic contacts with the polymeric side chains. , A few nonacidic hydrophobic drugs have also been solubilized using this polymer. , Therefore, by judicial choice of the correct functional groups, it should be possible to help solubilize KHIs, which are predominantly polyamides.…”
Section: Polymeric Dispersantsmentioning
confidence: 99%
“…One example is a class of terpolymers mostly consisting of three methacrylate monomers: butyl methacrylate, 2-dimethylaminoethyl methacrylate, and methyl methacrylate (see Figure 9). 123,124 The polymer by itself is soluble in water or brines at pH values of 5−6 or less. This polymer is particularly helpful at solubilization acidic drugs via ionic interactions (e.g., protonated amine moieties) and by multiple hydrophobic contacts with the polymeric side chains.…”
Section: ■ Osmolytes or Antidenaturantsmentioning
confidence: 99%
“…EUD-E is widely used for moisture protection coating and taste masking in pharmaceutical formulation. 20 Furthermore, because EUD-E has strong crystallization inhibition 21 and drug solubilization abilities, 22,23 its application as a polymeric carrier of solid dispersion has attracted great attention. We reported that EUD-E significantly improved the stability of mefenamic acid (MFA) in its amorphous state in solid dispersion according to the ionic interaction between MFA and EUD-E. 24 Moreover, the maintenance of a high MFA concentration after dispersing the solid dispersion into water and subsequent bioavailability enhancement in vivo study using rats were demonstrated.…”
Section: ■ Introductionmentioning
confidence: 99%